Developing a nontoxic and biocompatible polymeric self-assembly by using RAFT methodology for biomedical application. (March 2019) - Deepak,; Sharma, Swati; Kumar, Ashok; Kumar, Rajesh; Nandy, Koushik; Srivastava, Arti; Tomar, Munendra Singh; Acharya, Arbind
Graphical abstract: Highlights: The PVP-b-PVK copolymer has been successfully polymerized by RAFT methdology using new synthesized BPDC as CTA. It shows amphiphilic nature in aqueous media, having CMC value 0.014 - 0.052 mg/mL for Mw. 40000- 323000 g/mol. The toxic test results showed no cytotoxicity at higher concentration of polymer, so it can be used for drug delivery purpose. The primary results of cytotoxicity (6 h and 24 h) may support for the use in biomedical applications. The hydrophilic drug levofloxacin could be encapsulated into the polymeric micelles via making beads of sodium alginate. Control release of Levofloxacin from the beads in a period of 7 h up to 63.0 % at pH 7.4 & 37 °C. Abstract: The amphiphilic block copolymer poly( N -vinylpyrrolidone)-b-poly( N -vinylcarbazole) (PVP-b-PVK) was synthesized by reversible-deactivation radical polymerization (RDRP)using reversible addition-fragmentation chain transfer (RAFT) methodology by new chain transfer agent (CTA) i.e. benzyl piperidine dithiocarbamate (BPDC). The pseudo-first-order kinetics and linear evolution of the molar mass with N -vinylpyrrolidone (NVP) conversion were obtained with the molar mass dispersity (Ð) 1.30–1.41 in toluene. 1 H NMR spectrum indicates the presence of chain-end functional groups on homopolymer and block copolymer. The above block copolymer get self-assembled and form micelles in the aqueous medium, the size of micelles is characterized by 1 H NMR, transmission electron micrographs (TEM) and dynamic laser light scattering (DLS) analyses, and critical micelles concentration (CMC) was determined by UV–vis spectroscopy. Trypan blue exclusion and MTT assay were done to ensure the cytotoxic effect of PVP-b-PVK on different types of normal cells (thymocytes, splenocytes and macrophage), and no cytotoxic effect was shown by block copolymer on cells, while observed biocompatibility with cells was 200 mg/mL. Further, the beads of block copolymer releases (65%) highly water-soluble levofloxacin drug up to 8 h in a controlled manner at pH 7.4 (37 ± 0.2 °C), while loading of levofloxacin drug was 62% (w/w).